The new life path of world languages or national language corporations - Mahammadiyeva Diyora (Genius Journals, 2022)
This article highlights the importance of using the language corpus for representatives of various fields if we create a national corpus of the Uzbek language. It has been proven how important the corpus is for lexicographers, literary critics, teachers, programmers, journalists, pragmalinguists, forensic linguists
Keywords: Digitization process; language corpus; electronic library; educational corpus